UWB’s Big Leap: The Niche Tech Set to Disrupt IoT Connectivity - Dan-Alex Ceausescu-Constantinescu; Claudiu Chiriac (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
With a history of over two centuries, ultra-wideband seems to be on the verge of influencing the IoT and revolutionizing how devices communicate with each other. Unlike other technologies, Ultra-Wideband does not seem to be the technology that will solve all the issues, but rather a niche technology that will have a high impact in a niche domain. The current article analyses the Ultra-Wideband technology from its debut in the mobile world, current applications, main players in the market both in terms of Ultra-Wideband ecosystems and producers, and how the trackers market looked before the Ultra-Wideband trackers went mainstream.